Vroom's Expectancy Theory. An Empirical Study: Civil Servant's Performance Appraisal Influencing Expectancy - Leonina Emilia SUCIU; Maria MORTAN; Lucreţia LAZĂR (Transylvanian Review of Administrative Sciences, 2013)
This study aims to highlight the importance of performance evaluation from the perspective of work motivation. The research is based on the expectancy theory developed by Victor Vroom and is meant to show that performance evaluation influences one of the factors from the VIE model, the expectancy. The empirical part of the research aims to show the above mentioned in the context of local public administration, namely in the case of the Romanian civil servants from the North-West Region. We have presented the particularities of civil servants performance evaluation in the Romanian local public administration, and its connection to their expectancy and work motivation. The results have shown that civil servants performance appraisal influences civil servants expectancy and this in its turn influences their work motivation.